Update public sector information accessibility policies and open data licences in Europa - Welle Donker, Frederika (A+BE | Architecture and the Built Environment, 2016)
Chapters 2, 3 and 5 of this dissertation were written between 2007 and 2009. Since then, there have been a number of developments in the field of public sector information re-use. One of these developments is the emergence of open data. In the previous chapters, legal and financial aspects of public sector information access regimes were discussed. This chapter starts with a description of the revised PSI Directive 2013/37/EU of the European Parliament and of the Council of 26 June 2013 amending Directive 2003/98/EC on the re-use of public sector information. This Directive and Directive 2007/2/EC of the European Parliament and of the Council of 14 March 2007 establishing an Infrastructure for Spatial Information in the European Community (INSPIRE) provide the basis for implementing open data policies, as described in Chapters 6, 7 and 8. This chapter continues with an update of the licence framework discussed in Chapter 3. This update was written for the European Location Framework project. The chapter concludes with an analysis of the various open data licences currently in use in Europe.